Half-Sandwich Ru(II) and Os(II) Bathophenanthroline Complexes Containing a Releasable Dichloroacetato Ligand - Štarha, Pavel; Trávníček, Zdeněk; Vančo, Ján; Dvořák, Zdeněk (Molecules (Basel, Switzerland), 2018)
We report on the preparation and thorough characterization of cytotoxic half-sandwich complexes [Ru(η⁶-pcym)(bphen)(dca)]PF₆ (Ru-dca) and [Os(η⁶-pcym)(bphen)(dca)]PF₆ (Os-dca) containing dichloroacetate(1-) (dca) as the releasable O-donor ligand bearing its own cytotoxicity; pcym = 1-methyl-4-(propan-2-yl)benzene (p-cymene), bphen = 4,7-diphenyl-1,10-phenanthroline (bathophenanthroline). Complexes Ru-dca and Os-dca hydrolyzed in the water-containing media, which led to the dca ligand release (supported by ¹H NMR and electrospray ionization mass spectra). Mass spectrometry studies revealed that complexes Ru-dca and Os-dca do not interact covalently with the model proteins cytochrome c and lysozyme. Both complexes exhibited slightly higher in vitro cytotoxicity (IC50 = 3.5 μM for Ru-dca, and 2.6 μM for Os-dca) against the A2780 human ovarian carcinoma cells than cisplatin (IC50 = 5.9 μM), while their toxicity on the healthy human hepatocytes was found to be IC50 = 19.1 μM for Ru-dca and IC50 = 19.7 μM for Os-dca. Despite comparable cytotoxicity of complexes Ru-dca and Os-dca, both the complexes modified the cell cycle, mitochondrial membrane potential, and mitochondrial cytochrome c release by a different way, as revealed by flow cytometry experiments. The obtained results point out the different mechanisms of action between the complexes.
Keywords: uvolňování léčiv; Phenanthrolines; ruthenium; Coordination Complexes; flow cytometry; Dichloroacetic Acid; Ligands; osmium; proliferace buněk; lidé; nádory vaječníků; Ruthenium; cytotoxicity; Cell Proliferation; Ovarian Neoplasms; ženské pohlaví; ligandy; Drug Liberation; dichloroacetate(1–); fenantroliny; kyselina dichloroctová; Osmium; komplexní sloučeniny; Humans; half-sandwich; Female